PRECREST: a phase II prevention and biomarker trial of creatine in at-risk Huntington disease - Rosas, Herminia D; Doros, Gheorghe; Gevorkian, Sona; Malarick, Keith; Reuter, Martin; Coutu, Jean-Philippe; Triggs, Tyler D; Wilkens, Paul J; Matson, Wayne; Salat, David H; Hersch, Steven M (Neurology, 2014)
To assess the safety and tolerability of high-dose creatine, the feasibility of enrolling premanifest and 50% at-risk subjects in a prevention trial, and the potential of cognitive, imaging, and blood markers. Sixty-four eligible consenting participants were randomly allocated (1:1) to 15 g twice daily of creatine monohydrate or placebo for a 6-month double-blind phase followed by a 12-month open-label extension. Subjects included premanifest (tested) and at-risk (not tested) individuals without clinical symptoms or signs of Huntington disease (HD). Primary outcomes were safety and tolerability. Exploratory endpoints included fine motor, visuospatial, and memory performance; structural and diffusion MRI; and selected blood markers. Forty-seven HD carriers and 17 non-HD controls were enrolled. Fifteen discontinued treatment (2 assigned to placebo); all were followed for the entire study period. Primary analysis was by intent to treat. The most common adverse events were gastrointestinal. Neuroimaging demonstrated treatment-related slowing of cortical and striatal atrophy at 6 and 18 months. We describe a design that preserves the autonomy of subjects not wanting genetic testing while including controls for assessing the specificity of treatment effects. Our results demonstrate the feasibility of prevention trials for HD and the safety of high-dose creatine, provide possible evidence of disease modification, support future studies of creatine, and illustrate the value of prodromal biomarkers. This study provides Class I evidence that high-dose creatine is safe and tolerable.